High-toughness flame-retardant foaming type PVC wood-plastic plate and preparation method thereof

By forming a PVC/polyurethane interpenetrating network structure in PVC wood-plastic composite materials, and introducing wood fibers, nanofillers and flame retardants, the problems of insufficient toughness and flammability of traditional PVC wood-plastic materials are solved, and foamed PVC wood-plastic boards with high toughness and good flame retardant properties are achieved.

CN119613886AInactive Publication Date: 2025-03-14ANHUI AIYALUN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411793093.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PVC wood-plastic composite materials have problems such as insufficient toughness and flammability, which limits their application in certain special environments.

Method used

By mixing the PVC resin and the polyurethane prepolymer in a certain proportion, a PVC/polyurethane interpenetrating network structure is formed, and wood fibers, nanofillers and flame retardant are introduced to prepare a high-toughness flame retardant foamed PVC wood-plastic board.

Benefits of technology

This material not only enhances mechanical strength and impact resistance, but also greatly improves toughness and flame retardant properties, making it suitable for applications in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613886A_ABST
    Figure CN119613886A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness flame-retardant foaming type PVC wood-plastic plate and a preparation method thereof, and belongs to the technical field of building materials. The high-toughness flame-retardant foaming type PVC wood-plastic plate comprises the following components in percentage by mass: 30%-50% of PVC resin, 20%-40% of a polyurethane prepolymer, 5%-30% of wood fibers, 2%-10% of a nano filler, 2%-10% of a flame retardant, 1%-5% of a plasticizer, 0.5%-2% of a foaming agent and 0-1% of other auxiliaries, and the PVC resin and the polyurethane prepolymer form an interpenetrating network structure. According to the invention, the PVC resin and the polyurethane prepolymer are mixed according to a certain proportion to form a PVC / polyurethane interpenetrating network structure, which not only enhances the mechanical strength of the material, but also greatly improves the toughness and impact resistance of the material; the introduction of the nanofiller further enhances the interface bonding force and stress dispersion capability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a high-toughness flame-retardant foamed PVC wood-plastic board and a preparation method thereof. Background Art

[0002] PVC wood-plastic composites have attracted wide attention due to their excellent physical and chemical properties, good processing performance and environmental protection characteristics. However, traditional PVC wood-plastic composites have problems such as insufficient toughness and easy burning, which limits their application in certain special environments. Therefore, the development of a foamed PVC wood-plastic board with high toughness and good flame retardant properties has become a market demand. Summary of the invention

[0003] The object of the present invention is to provide a high-toughness flame-retardant foamed PVC wood-plastic board and a preparation method thereof. By mixing PVC resin and polyurethane prepolymer in a certain proportion, a PVC / polyurethane interpenetrating network structure is formed. This structure not only enhances the mechanical strength of the material, but also greatly improves its toughness and impact resistance, thereby solving the problems raised in the above-mentioned background technology.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-toughness flame-retardant foamed PVC wood-plastic board, characterized in that it comprises the following components in mass percentage: 30%-50% of PVC resin, 20%-40% of polyurethane prepolymer, 5%-30% of wood fiber, 2%-10% of nano filler, 2%-10% of flame retardant, 1%-5% of plasticizer, 0.5%-2% of foaming agent and 0-1% of other additives, wherein the PVC resin and the polyurethane prepolymer form an interpenetrating network structure.

[0005] Preferably, the preparation method of the polyurethane prepolymer is as follows: add polyether polyol to a blender, start the blender to ensure that it is fully dispersed, add a catalyst, a crosslinking agent, an antioxidant and a light stabilizer in sequence, continue stirring until uniform, slowly add MDI while keeping stirring. MDI has a high reactivity, so the addition speed needs to be controlled to avoid too fast a reaction that causes the material to solidify. The mixture is heated to 70-80°C and kept stirring to allow MDI to react preliminarily with the polyether polyol to form a prepolymer. The reaction time is 30-60 minutes. After the reaction is completed, the prepolymer is cooled to room temperature for standby use.

[0006] Preferably, the ratio of MDI to polyether polyol in the polyurethane prepolymer is 1:1.5, and all raw materials used in the polyurethane prepolymer are fully dried before use to avoid moisture affecting the reaction, and are dried at 60° C. for 4 hours.

[0007] Preferably, the wood fiber is at least one of bamboo fiber, coconut shell fiber, cotton fiber, palm fiber, sisal fiber, pine needle fiber and abaca fiber. These fibers have strong toughness and are suitable for manufacturing high-strength composite materials. At the same time, the surface is relatively rough, which can enhance the interfacial bonding force with the polymer matrix.

[0008] Preferably, the nanofiller includes at least one of nanoclay, nanosilica, carbon nanotubes or graphene. The small size effect of the nanoparticles enables them to be evenly dispersed in the PVC matrix, enhancing the interfacial bonding force, and when subjected to external forces, they can effectively transfer and disperse stress and improve the toughness of the material.

[0009] Preferably, the nanofiller needs to be modified before use, and the modification method is as follows: a silane coupling agent is dissolved in a solvent to prepare a modified solution with a concentration of 1-5wt%, the nanofiller is dispersed in the modified solution, stirred evenly and allowed to stand for 1-2 hours to allow the silane coupling agent to be fully adsorbed on the surface of the nanofiller, the impregnated nanofiller is dried at 60-80°C for 2-4 hours to remove excess solvent and unreacted silane coupling agent, and in order to promote chemical bonding between the silane coupling agent and the surface of the nanofiller, a heat treatment is performed at 100-150°C for 0.5-1 hour. The silane coupling agent can form a stable chemical bond on the surface of the nanofiller, significantly improving the interfacial bonding force. The modified nanofiller is more easily dispersed evenly in the PVC matrix to avoid agglomeration.

[0010] Preferably, the flame retardant is an intumescent flame retardant.

[0011] Preferably, the other additives include at least one of a stabilizer, a lubricant, an antioxidant, and a light stabilizer to improve processing performance and extend service life.

[0012] Another technical problem to be solved by the present invention is to provide a method for preparing a high-toughness flame-retardant foamed PVC wood-plastic board, comprising the following steps:

[0013] Step 1: All raw materials are dried at 60° C. for 4 hours to prepare a polyurethane prepolymer for later use, and the nanofiller is modified for later use;

[0014] Step 2: Add PVC resin, plasticizer, flame retardant, wood fiber, part of foaming agent and other additives into a twin-screw extruder, fully mix at a temperature of 160-180°C to form a uniform PVC matrix. During the melting and plasticization process of the PVC matrix, gradually add the modified nanofiller to ensure its uniform dispersion;

[0015] Step 3: Continue to heat the mixed PVC matrix to 180-190°C to completely melt and plasticize it, and initially shape it into a sheet or strip. Rapidly cool the initially formed PVC matrix to room temperature to fix its shape and prevent deformation during the subsequent reaction process;

[0016] Step 4: Inject the prepared polyurethane prepolymer directly into the formed PVC matrix through an injection device. The polyurethane prepolymer diffuses in the PVC matrix and begins to cross-link. Put the PVC matrix injected with the polyurethane prepolymer into the mold and keep it at a temperature of 75-85°C for 2 hours to ensure that the PU is fully cross-linked and forms a complete three-dimensional network.

[0017] Step 5: Add the remaining foaming agent into the PVC / polyurethane mixture through an injection device, raise the temperature to 180-200°C, decompose the foaming agent and generate gas to form a uniform foaming structure, and anneal the sheet at 65°C for 2.5 hours to further eliminate internal stress and improve the toughness and dimensional stability of the material.

[0018] Preferably, the foaming agent is added in two times, and the first addition amount accounts for 20-30% of the total foaming amount to ensure that it is evenly dispersed in the PVC matrix.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention discloses a high-toughness flame-retardant foamed PVC wood-plastic board and a preparation method thereof. PVC resin and polyurethane prepolymer are mixed in a certain proportion to form a PVC / polyurethane interpenetrating network structure, which not only enhances the mechanical strength of the material, but also greatly improves its toughness and impact resistance. The introduction of nanofillers further enhances the interface bonding force and stress dispersion ability of the material. The modified nanofillers can be evenly dispersed in a PVC matrix to avoid agglomeration, thereby effectively improving the overall toughness of the material. The three-dimensional network structure of polyurethane can effectively fix the flame retardant to prevent the flame retardant from being lost during combustion, thereby ensuring the durability of the flame retardant effect. The invention selects natural wood fibers as filling materials. These fibers not only have strong toughness and can enhance the mechanical properties of the material, but also have a relatively rough surface of the wood fibers, which can form a stronger interface bonding force with the polymer matrix, thereby further improving the overall performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a flow chart for preparing the high-toughness flame-retardant foamed PVC wood-plastic board. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1:

[0024] In order to solve the problem of insufficient toughness and easy burning of existing PVC wood-plastic composite materials, which limits their application in some special environments, please refer to Figure 1 , this embodiment provides the following technical solutions:

[0025] A high-toughness flame-retardant foamed PVC wood-plastic board, using the following raw materials in percentage by mass:

[0026] PVC resin: 40%

[0027] Polyurethane prepolymer: 25%

[0028] Bamboo fiber: 20%

[0029] Nanoclay: 5%

[0030] Intumescent flame retardant: 5%

[0031] Dioctyl phthalate: 3%

[0032] Azodicarbonamide: 1.5%

[0033] Stabilizer, lubricant, antioxidant, light stabilizer: 0.5% for preparation, the specific method is as follows:

[0034] Raw material drying: All raw materials were dried at 60°C for 4 hours.

[0035] Preparation of polyurethane prepolymer:

[0036] Add polyether polyol to the mixer, start the mixer to ensure that it is fully dispersed, add catalyst, crosslinking agent, antioxidant and light stabilizer in turn, continue stirring until uniform, slowly add MDI, the ratio of MDI to polyether polyol is 1:1.5, keep stirring at the same time, control the addition speed to avoid too fast reaction causing material solidification, heat the mixture to 75°C, keep stirring, allow MDI and polyether polyol to react initially to form prepolymer, the reaction time is 45 minutes, after the reaction is completed, cool the prepolymer to room temperature for use.

[0037] Nanofiller modification:

[0038] The silane coupling agent is dissolved in a solvent to prepare a modified solution with a concentration of 3wt%, and the nanoclay is dispersed in the modified solution. After being stirred evenly, the solution is allowed to stand for 1.5 hours to allow the silane coupling agent to be fully adsorbed on the surface of the nanoclay. The impregnated nanoclay is dried at 70°C for 3 hours to remove excess solvent and unreacted silane coupling agent, and is heat treated at 120°C for 0.8 hours to promote chemical bonding between the silane coupling agent and the surface of the nanoclay.

[0039] PVC matrix preparation:

[0040] PVC resin, plasticizer, flame retardant, bamboo fiber, 25% foaming agent and other additives are added to a twin-screw extruder and fully mixed at a temperature of 170°C to form a uniform PVC matrix. During the melting and plasticizing process of the PVC matrix, the modified nanoclay is gradually added to ensure its uniform dispersion. The mixed PVC matrix is ​​further heated to 185°C to make it completely melted and plasticized, and initially formed into a sheet. The initially formed PVC matrix is ​​quickly cooled to room temperature to fix its shape.

[0041] Interpenetrating network structure formation:

[0042] The pre-prepared polyurethane prepolymer is directly injected into the formed PVC matrix through an injection device. The polyurethane prepolymer diffuses in the PVC matrix and begins to cross-link. The PVC matrix injected with the polyurethane prepolymer is placed in a mold and kept at 80°C for 2 hours to ensure that the PU is fully cross-linked and forms a complete three-dimensional network.

[0043] Foaming treatment:

[0044] The remaining foaming agent is added to the PVC / polyurethane mixture through an injection device, and the temperature is raised to 190°C to decompose the foaming agent and generate gas to form a uniform foaming structure. The board is annealed at 65°C for 2.5 hours to produce a high-toughness flame-retardant foamed PVC wood-plastic board.

[0045] Embodiment 2:

[0046] A high-toughness flame-retardant foamed PVC wood-plastic board, using the following raw materials in percentage by mass:

[0047] PVC resin: 30%

[0048] Polyurethane prepolymer: 35%

[0049] Coconut shell fiber: 20%

[0050] Nano silicon dioxide: 5%

[0051] Intumescent flame retardant: 5%

[0052] Dioctyl phthalate: 3%

[0053] Azodicarbonamide: 1.5%

[0054] Stabilizer, lubricant, antioxidant, light stabilizer: 0.5% for preparation, the specific method is as follows:

[0055] Raw material drying: All raw materials were dried at 60°C for 4 hours.

[0056] Preparation of polyurethane prepolymer: same as in Example 1.

[0057] Nanofiller modification: Same as Example 1.

[0058] PVC matrix preparation:

[0059] Add PVC resin, plasticizer, flame retardant, coconut shell fiber, 20% foaming agent and other additives into a twin-screw extruder, fully mix at a temperature of 175°C to form a uniform PVC matrix. During the melting and plasticizing process of the PVC matrix, gradually add modified nano-silicon dioxide to ensure its uniform dispersion. Continue to heat the mixed PVC matrix to 188°C to make it completely melted and plasticized, and initially molded into sheets. The initially molded PVC matrix is ​​quickly cooled to room temperature to fix its shape.

[0060] Interpenetrating network structure formation:

[0061] The pre-prepared polyurethane prepolymer is directly injected into the formed PVC matrix through an injection device. The polyurethane prepolymer diffuses in the PVC matrix and begins to cross-link. The PVC matrix injected with the polyurethane prepolymer is placed in a mold and kept at 80°C for 2 hours to ensure that the PU is fully cross-linked and forms a complete three-dimensional network.

[0062] Foaming treatment:

[0063] The remaining foaming agent is added to the PVC / polyurethane mixture through an injection device, and the temperature is raised to 195°C to decompose the foaming agent and generate gas to form a uniform foaming structure. The board is annealed at 65°C for 2.5 hours.

[0064] Embodiment three:

[0065] A high-toughness flame-retardant foamed PVC wood-plastic board, using the following raw materials in percentage by mass:

[0066] PVC resin: 30%

[0067] Polyurethane prepolymer: 40%

[0068] Sisal fiber: 15%

[0069] Carbon nanotubes: 5%

[0070] Intumescent flame retardant: 5%

[0071] Dioctyl phthalate: 3%

[0072] Azodicarbonyl: 1.5%

[0073] Stabilizer, lubricant, antioxidant, light stabilizer: 0.5% for preparation, the specific method is as follows:

[0074] Raw material drying: All raw materials were dried at 60°C for 4 hours.

[0075] Preparation of polyurethane prepolymer: same as in Example 1.

[0076] Nanofiller modification: Same as Example 1.

[0077] PVC matrix preparation:

[0078] PVC resin, plasticizer, flame retardant, sisal fiber, 20% foaming agent and other additives are added to a twin-screw extruder and fully mixed at a temperature of 180°C to form a uniform PVC matrix. During the melting and plasticizing process of the PVC matrix, the modified carbon nanotubes are gradually added to ensure their uniform dispersion. The mixed PVC matrix is ​​further heated to 190°C to make it completely melted and plasticized, and initially formed into a sheet. The initially formed PVC matrix is ​​quickly cooled to room temperature to fix its shape.

[0079] Interpenetrating network structure formation:

[0080] The pre-prepared polyurethane prepolymer is directly injected into the formed PVC matrix through an injection device. The polyurethane prepolymer diffuses in the PVC matrix and begins to cross-link. The PVC matrix injected with the polyurethane prepolymer is placed in a mold and kept at 85°C for 2 hours to ensure that the PU is fully cross-linked and forms a complete three-dimensional network.

[0081] Foaming treatment:

[0082] The remaining foaming agent is added to the PVC / polyurethane mixture through an injection device, and the temperature is raised to 200°C to decompose the foaming agent and generate gas to form a uniform foaming structure. The board is annealed at 65°C for 2.5 hours.

[0083] By further increasing the content of polyurethane prepolymer to 40%, a denser interpenetrating network structure of PVC and PU is formed, and the toughness and impact resistance of the material reach the optimal level. The elongation at break is as high as 220%, indicating that the material has extremely excellent flexibility and deformation resistance, and is suitable for applications in extreme environments. In addition, the addition of carbon nanotubes further enhances the mechanical properties and electrical conductivity of the material, broadening its application range.

[0084] The high-toughness flame-retardant foamed PVC wood-plastic board prepared in the above embodiment was tested to obtain the following data:

[0085] Tensile Strength Impact strength Elongation at break Oxygen Index Embodiment 1 35MPa <![CDATA[12kJ / m 2 ]]> 150% 30% Embodiment 2 38MPa <![CDATA[15kJ / m 2 ]]> 180% 32% Embodiment 3 42MPa <![CDATA[18kJ / m 2 ]]> 220% 35%

[0086] In Example 1, 25% of polyurethane prepolymer is introduced to form an interpenetrating network structure of PVC and polyurethane, which significantly improves the toughness and impact resistance of the material. In Example 2, the interpenetrating network structure of PVC and PU is further enhanced by increasing the content of polyurethane prepolymer to 35%, so that the toughness and impact resistance of the material are more significantly improved, and the elongation at break reaches 180%, showing that the material has extremely high flexibility and deformation resistance, and is suitable for application scenarios with high strength requirements. In Example 3, a denser interpenetrating network structure of PVC and PU is formed by further increasing the content of polyurethane prepolymer, and at the same time, the materials of wood fiber and nanofiller are changed, and the toughness and impact resistance reach the optimal level, which is suitable for applications in extreme environments. The addition of carbon nanotubes further enhances the mechanical properties and conductive properties of the material, broadening its application range.

[0087] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0088] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. A high-toughness flame-retardant foamed PVC wood-plastic board, characterized in that: The invention comprises the following components in percentage by mass: 30%-50% of PVC resin, 20%-40% of polyurethane prepolymer, 5%-30% of wood fiber, 2%-10% of nano filler, 2%-10% of flame retardant, 1%-5% of plasticizer, 0.5%-2% of foaming agent and 0-1% of other additives. The PVC resin and the polyurethane prepolymer form an interpenetrating network structure.

2. The high-toughness flame-retardant foamed PVC wood-plastic board according to claim 1, characterized in that: The preparation method of the polyurethane prepolymer is as follows: adding polyether polyol into a stirrer, starting the stirrer to ensure that it is fully dispersed, adding a catalyst, a crosslinking agent, an antioxidant and a light stabilizer in sequence, continuing to stir until uniform, slowly adding MDI while keeping stirring, heating the mixture to 70-80° C., keeping stirring, allowing MDI and polyether polyol to react initially to form a prepolymer, the reaction time is 30-60 minutes, and after the reaction is completed, cooling the prepolymer to room temperature for standby use.

3. The high-toughness flame-retardant foamed PVC wood-plastic board according to claim 2, characterized in that: The ratio of MDI to polyether polyol in the polyurethane prepolymer is 1:1.

5. All raw materials used in the polyurethane prepolymer are fully dried before use, and are dried at 60° C. for 4 hours.

4. The high-toughness flame-retardant foamed PVC wood-plastic board according to claim 3, characterized in that: The wood fiber is at least one of bamboo fiber, coconut shell fiber, cotton fiber, palm fiber, sisal fiber, pine needle fiber and abaca fiber.

5. The high-toughness flame-retardant foamed PVC wood-plastic board according to claim 4, characterized in that: The nanofiller includes at least one of nanoclay, nanosilicon dioxide, carbon nanotube or graphene.

6. The high-toughness flame-retardant foamed PVC wood-plastic board according to claim 5, characterized in that: The nanofiller needs to be modified before use, and the modification method is as follows: a silane coupling agent is dissolved in a solvent to prepare a modified solution with a concentration of 1-5wt%, the nanofiller is dispersed in the modified solution, stirred evenly and allowed to stand for 1-2 hours to allow the silane coupling agent to be fully adsorbed on the surface of the nanofiller, the impregnated nanofiller is dried at 60-80°C for 2-4 hours, excess solvent and unreacted silane coupling agent are removed, and heat treatment is performed at 100-150°C for 0.5-1 hour.

7. The high-toughness flame-retardant foamed PVC wood-plastic board according to claim 6, characterized in that: The flame retardant is an intumescent flame retardant.

8. The high-toughness flame-retardant foamed PVC wood-plastic board according to claim 7, characterized in that: The other auxiliary agents include at least one of a stabilizer, a lubricant, an antioxidant, and a light stabilizer.

9. A method for preparing a high-toughness flame-retardant foamed PVC wood-plastic board according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: All raw materials are dried at 60° C. for 4 hours to prepare a polyurethane prepolymer for later use, and the nanofiller is modified for later use; Step 2: Add PVC resin, plasticizer, flame retardant, wood fiber, part of foaming agent and additives into a twin-screw extruder, fully mix at a temperature of 160-180°C to form a uniform PVC matrix. During the melting and plasticization process of the PVC matrix, gradually add the modified nanofiller to ensure its uniform dispersion; Step 3: Continue to heat the mixed PVC matrix to 180-190°C, completely melt and plasticize it, and initially shape it into sheets or strips. Rapidly cool the initially formed PVC matrix to room temperature to fix its shape and prevent deformation during subsequent reactions; Step 4: Inject the prepared polyurethane prepolymer into the formed PVC matrix through an injection device. The polyurethane prepolymer diffuses in the PVC matrix and begins to cross-link. Put the PVC matrix injected with the polyurethane prepolymer into the mold and keep it at a temperature of 75-85°C for 2 hours to ensure that the PU is fully cross-linked and forms a complete three-dimensional network. Step 5: Add the remaining foaming agent into the PVC / polyurethane mixture through an injection device, raise the temperature to 180-200°C, decompose the foaming agent and generate gas to form a uniform foaming structure, and anneal the sheet at 65°C for 2.5 hours.

10. The method for preparing the high-toughness flame-retardant foamed PVC wood-plastic board according to claim 9, characterized in that: The foaming agent is added in two times, and the first addition accounts for 20-30% of the total foaming agent amount.

Citation Information

Cited By

  • Functional ceramic blank and preparation method thereof

    CN120398569A

  • A functional ceramic green body and a method for preparing the same

    CN120398569B

  • Flame-retardant wood-plastic composite material and preparation method thereof

    CN120552445A